2022
DOI: 10.3390/plants11020228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Amendments in Soil on Physiological and Biochemical Attributes of Vachellia nilotica and Dalbergia sissoo under Saline Stress

Abstract: Vachellia nilotica (L.) P.J.H. Hurther & Mabb. and Dalbergia sissoo Roxb. are two of the most important multipurpose agroforestry tree species of the Indian sub-continent, but their growth in saline soils is greatly reduced. Recently, organic amendments have showed the potential to increase plant growth in salt-affected soils; however, the influence of using these amendments for growing the above-mentioned tree species under saline conditions is not yet quantified. Therefore, an experiment was devised to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 91 publications
1
2
0
1
Order By: Relevance
“…Macci, Doni [ 28 ], however, found that organic fertilizer was more effective in increasing soil organic matter content and microbial activity than inorganic fertilizer. Similar findings have been made by other researchers showing that organic nutrients are more likely to be released into the environment slowly and for a longer period, and with a beneficial impact on the soil microbiome [ 29 , 30 , 31 ]. For pollutant cleanup, biostimulation with either organic nutrients or with a combination of organic and inorganic nutrients has been proven to be more productive because it not only provides nutrients to microbes, but also enriches the soil[ 32 ].…”
Section: Introductionsupporting
confidence: 89%
“…Macci, Doni [ 28 ], however, found that organic fertilizer was more effective in increasing soil organic matter content and microbial activity than inorganic fertilizer. Similar findings have been made by other researchers showing that organic nutrients are more likely to be released into the environment slowly and for a longer period, and with a beneficial impact on the soil microbiome [ 29 , 30 , 31 ]. For pollutant cleanup, biostimulation with either organic nutrients or with a combination of organic and inorganic nutrients has been proven to be more productive because it not only provides nutrients to microbes, but also enriches the soil[ 32 ].…”
Section: Introductionsupporting
confidence: 89%
“…In saline soils, the addition of plant residues increases microbial activity and biomass temporarily; as a result, microbial activity and biomass return to values similar to those in the unamended soils [5]. Similarly, previous studies have reported that application of plant residues could mitigate the effects of salinity on soil microbial properties under laboratory conditions [13] and also could improve soil fertility [48].…”
Section: Introductionmentioning
confidence: 82%
“…Between Fe 2 SO 4 and peat moss alone, the former produced more vegetative growth in P. x alkinsiana. Soil amendments enhance soil chemical, physical, and even biological characteristics and may provide essential elements required by plants [33]. The addition of Fe 2 SO 4 to soil may reduce SAR by increasing CaCO 3 solubility, which in turn replaces Na + ions [20].…”
Section: Discussionmentioning
confidence: 99%